Facile Fabrication of Flexible Microsupercapacitor with High Energy Density. Issue 9 (11th October 2016) - Liu, Yuqing; Weng, Bo; Xu, Qun; Hou, Yuyang; Zhao, Chen; Beirne, Stephen; Shu, Kewei; Jalili, Rouhollah; Wallace, Gordon G.; Razal, Joselito M.; Chen, Jun
Abstract : Flexible microsupercapacitors (fMSCs) with interdigitated electrode design are a promising platform as a power source or energy storage unit for wearable microelectronics. In this work, a facile fabrication of all‐solid‐state fMSCs is reported through a combination of simple technologies including bar coating and laser etching, to generate the interdigitated patterned electrodes. These novel fMSC devices made with interdigitated patterned electrodes can deliver outstanding areal capacitance (84.7 mF cm −2 at 5 mV s −1 and 45.5 mF cm −2 at 200 mV −1 ), high volumetric capacitance (14.5 F cm −3 at 5 mV s −1 and 7.83 F cm −3 at 200 mV −1 ), and high cycling stability (94.3%, 10 000 cycles). In addition, the fabrication method employed allows for facile fabrication of various interconnects between several fMSCs on a single device, which enables for the required voltage and/or current output to be tuned easily prior to device fabrication. These fMSCs can power 20 light‐emitting diodes even when bent demonstrating versatility for practical applications. Abstract : Flexible microsupercapacitors (fMSCs) with different pattern designs are facilely fabricated via laser etching on flexible reduced graphene oxide‐poly(3, 4‐ethylenedioxythiophene)/poly(styrenesulfonate) films. Optimized fMSCs deliver high areal capacitance (84.7 mF cm −2 ), volumetric capacitance (14.5 F cm −3 ), and high cycling stability (94.3%, 10 000 cycles). Twelve tandem connected fMSCs can power 20 light‐emitting diodes even when bent demonstrating versatility for practical applications.